2020
DOI: 10.3389/fphar.2020.00367
|View full text |Cite
|
Sign up to set email alerts
|

Berberine Protects Against Simulated Ischemia/Reperfusion Injury-Induced H9C2 Cardiomyocytes Apoptosis In Vitro and Myocardial Ischemia/Reperfusion-Induced Apoptosis In Vivo by Regulating the Mitophagy-Mediated HIF-1α/BNIP3 Pathway

Abstract: Berberine (BBR) has a variety of pharmacological activities and is widely used in Asian countries. However, the clinical application of BBR still lacks scientific basis, what protective mechanism of BBR against myocardial ischemia-reperfusion injury (MIRI). In vitro experiments, BBR pretreatment regulated autophagy-related protein expression, induced cell proliferation and autophagosome formation, and reduced the mitochondrial membrane potential (DYm) increase in H9C2 cells. In vivo experiments, BBR reduced th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 38 publications
(41 reference statements)
1
54
0
Order By: Relevance
“…Recently, berberine extract or pure compound has gained much attention in the newly published research and is among the top pharmaceutical supplements on shelves [412]. The preclinical evidence from huge studies reveals the capability of berberine to treat many diseases [411,[413][414][415][416][417][418][419]. Thus, berberine is clinically studied for many diseases, such as diabetes [410,[420][421][422][423].…”
Section: Berberinementioning
confidence: 99%
“…Recently, berberine extract or pure compound has gained much attention in the newly published research and is among the top pharmaceutical supplements on shelves [412]. The preclinical evidence from huge studies reveals the capability of berberine to treat many diseases [411,[413][414][415][416][417][418][419]. Thus, berberine is clinically studied for many diseases, such as diabetes [410,[420][421][422][423].…”
Section: Berberinementioning
confidence: 99%
“…BNIP3, which is a pro-apoptotic protein and a member of Bcl-2 family, is the downstream of HIF-1 signal pathway ( Cai et al, 2017 ). HIF-1α/BNIP3 signaling pathway-induced-autophagy plays protective role during myocardial ischemia-reperfusion injury ( Zhu et al, 2020 ). HIF-1α/BNIP3 signaling pathway will be explored in our next study.…”
Section: Discussionmentioning
confidence: 99%
“…Matsushima et al ( 21 ) demonstrated that HIF-1α may protect cardiac fibroblasts from apoptosis and represent a potential therapeutic target for heart remodeling following hypoxic injury. Additionally, a number of studies have confirmed that HIF-1α prevents MIRI and has a cardioprotective effect ( 22 , 23 ).…”
Section: Roles Of Hif-1α In Mirimentioning
confidence: 98%